2019
DOI: 10.15252/embr.201847488
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of MICU 2 provides insight into Ca 2+ binding and MICU 1‐ MICU 2 heterodimer formation

Abstract: The mitochondrial calcium uniporter (MCU) complex mediates the uptake of Ca2+ into mitochondria. Its activity is regulated by a heterodimer of MICU1 and MICU2, two EF‐hand‐containing proteins that act as the main gatekeeper of the uniporter. Herein we report the crystal structure of human MICU2 at 1.96 Å resolution. Our structure reveals a dimeric architecture of MICU2, in which each monomer adopts the canonical two‐lobe structure with a pair of EF‐hands in each lobe. Both Ca2+‐bound and Ca2+‐free EF‐hands are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…Similarly, Arg221(MICU1)-Asp330(MICU2), in the heterodimer, would also be important for the heterodimerization and function, as consistent with previous results (Li et al, 2016). In the case of the other salt bridge, Asp231(MICU1)-Arg352(MICU2), Wu et al already reported that this salt bridge is essential for the heterodimerization of MICU1 and MICU2 in the apo state (Wu et al, 2019). Thus, we assumed that the F-F interface of the MICU1-MICU2 heterodimer is biologically relevant.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similarly, Arg221(MICU1)-Asp330(MICU2), in the heterodimer, would also be important for the heterodimerization and function, as consistent with previous results (Li et al, 2016). In the case of the other salt bridge, Asp231(MICU1)-Arg352(MICU2), Wu et al already reported that this salt bridge is essential for the heterodimerization of MICU1 and MICU2 in the apo state (Wu et al, 2019). Thus, we assumed that the F-F interface of the MICU1-MICU2 heterodimer is biologically relevant.…”
Section: Discussionsupporting
confidence: 89%
“…The tight interaction in the apo state of MICU1-MICU2 might hinder the conformational changes required for Ca 2+ binding, resulting in a lower Ca 2+ binding affinity in the MICU1-MICU2 heterodimer compared with that of the MICU1 homodimer. tissues (Plovanich et al, 2013;Paillard et al, 2017;Patron et al, 2019), MICUs in cells generally form MICU1-MICU2 heterodimers, which is consistent with prior biochemical studies showing that the MICU1-MICU2 heterodimer is more stable (K d = 224 nM in the apo state) compared with homodimers of MICU1 and MICU2 (Wagner et al, 2015;Patron et al, 2014;Matesanz-Isabel et al, 2016;Mallilankaraman et al, 2012b;Csordá s et al, 2013;Ahuja & Muallem, 2014;Wu et al, 2019;Kamer et al, 2017). In particular, it has been reported that MICU2 functions as a gatekeeper of the MCU for suppressing the cellular damage caused by excessive mitochondrial Ca 2+ influx Patron et al, 2014).…”
Section: Structural Comparison With Ca 2+ -Bound Homodimer Structure supporting
confidence: 83%
See 3 more Smart Citations